Analisis Bibliometrik terhadap Hubungan Berpikir Kritis dan Kecemasan Matematika dalam Literatur Ilmiah - Mazid, Arini Rufaida; ARYANTI, OKTAVIA; ARIFIN, ZAENAL; Suwarno, Muji (Prodi Pendidikan Matematika Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2026)
This study bibliometrically analyzes the relationship between critical thinking and mathematical anxiety using Google Scholar data through Publish or Perish, covering 2020–2026. From 983 documents, 46 articles were analyzed using VOSviewer to map publication trends, author collaboration networks, and keyword clustering. Publication trends were fluctuating, with a decline in 2021 attributed to the COVID-19 pandemic, followed by recovery in subsequent years. Publications were dominated by Indonesian local journals, with Miatun, A. as the most productive author. Two keyword clusters were identified, with